Isolation of phytochemical and pharmacological bioactive compounds from Mitragyna speciosa (Korth.): a scoping review - Kalifa Kafo, Anwar Salm; Mahayidin, Hasni; Zailan, Nur Fatin Zalikha; Zaidan, Uswatun Hasanah; Syed Azhar, Sharifah Nurfadhlin Afifah; Ramasamy, Rajesh; Hassan, Masriana (Universiti Putra Malaysia, 2023)
Introduction: This scoping review aimed to provide a comprehensive summary and evaluation of solvents and methods for the extraction of bioactive compounds with pharmacological properties from Mitragyna speciosa (M. speciosa) Korth. Methods: The relevant articles were screened on electronic databases such as Scopus, PubMed, and Science Direct and verified their qualities based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guideline. Results: We selected 41 articles according to two features; the extraction of bioactive compounds and pharmacological properties of M. speciosa extract that involved different solvents and methods. Evidence shows that methanol was the commonly used solvent along with the maceration process in the extraction of M. speciosa to obtain valuable bioactive compounds with clinical benefits. Alternatively, Soxhlet provides less exertion to the extraction process with similar value. Conclusion: Despite various potential modern techniques and solvents available, the synergy between traditional maceration and Soxhlet and methanol was found to potentially attain pharmacological values and bioactive substances in M. speciosa.